Uncoated and coated ZnO nanoparticle life cycle in synthetic seawater. (7th January 2014) - Gelabert, Alexandre; Sivry, Yann; Ferrari, Roselyne; Akrout, Assia; Cordier, Laure; Nowak, Sophie; Menguy, Nicolas; Benedetti, Marc F.
Abstract The increasing production of nanoparticles has raised strong concerns regarding their environmental release. In life cycle scenarios of nanoparticles, marine systems constitute one of the main final compartments, and the fate of nanoparticles in marine environments needs to be assessed. The dissolution kinetics of commercial uncoated and organic‐coated ZnO nanoparticles in synthetic seawater were investigated using the Donnan membrane technique and 1000‐Da pore size ultrafiltration. Uncoated nanoparticles reach a maximum dissolution within the first hour, approximately 24% of total ZnO at pH 8.2, and 4% at pH 7.7, followed by secondary carbonated phase precipitation (hydrozincite) until the system reaches a steady state after 30 d of interaction. Assuming a pseudo first‐order kinetics for hydrozincite precipitation allowed calculation of kinetics constant values k′p of −208 × 10−4 mol L−1 h−1 ± 15 × 10−4 mol L−1 h−1 (standard deviation) at pH 7.7, and −57 × 10−4 mol L−1 h−1 ± 11 × 10−4 mol L−1 h−1 at pH 8.2. The presence of an organic coating drastically modifies the life cycle of nanoparticles, with a maximum dissolution reached after 7 d of interaction, followed by a stationary phase lasting from 1 wk to 3 wk, and a subsequent Zn carbonate precipitation until a steady state is reached after 1.5 mo. Monitoring changes in the physicochemical parameters of nanoparticles after exposure to synthetic seawater constitutes an important step in predicting their fate in environmental systems, with major implications for ecotoxicological studies in which metallic speciation is required for toxicity evaluation. Environ Toxicol Chem 2014;33:341–349. © 2013 SETAC